KINERJA ORGANISASI DINAS PERTAMBANGAN DAN ENERGI PROVINSI KALIMANTAN BARAT - E.21109044, Widodo (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this study is the work load carried by each apparatus is uneven , this is due to lack of personnel and a limited amount of work infrastructures and adequate . Another problem is the lack of implementation of training followed by employees that result in low employee responsiveness to the duties and functions . From the research it was found that the performance of the organization of Mining and Energy of West Kalimantan Mining Sector in enhancing non-tax revenues are less than optimal . It is based on the results of a study that examined aspects tigas Baitu efficiency , effectiveness , and responsiveness Justice showed poor results . Responding to the suggestion that there is a phenomenon which recommended , among others : 1 ) the need for the implementation of education and training concerning the things that are special as training related to mining tax state revenue ( non-tax revenues ) due to the mining sector need a deep understanding of the tasks related to the mining sector so that the increase in non-tax revenues mining sector will be more effective and efficient , 2 ) need a heightened awareness of officers at the Department of Mines and Energy of West Kalimantan Province so that the implementation tasks become responsibilities can be well understood . 3 ) to improve responsiveness tarhadap entrepreneurs , leaders at the Department of Mines and Energy of the Province of West Kalimantan in order to improve the oversight and guidance to the holders of Mining Permit ( IUP ) so that the entrepreneur is aware of its obligation to pay a fixed contribution of mining to the achievement of revenue targets Non-tax ( non-tax revenues ) mining sector in West KalimantanÂ Keywords : Efficiency , Effectiveness , Fairness, Responsiveness